Strategic Games and Algorithmic Secrecy - Cofone, Ignacio; Strandburg, Katherine (McGill Law Journal / Revue de droit de McGill, 2019)
We challenge a claim commonly made by industry and government representatives and echoed by legal scholarship: that algorithmic decision-making processes are better kept opaque or secret because otherwise decision subjects will “game the system”, leading to inaccurate or unfair results. We show that the range of situations in which people are able to game decision-making algorithms is narrow, even when there is substantial disclosure. We then analyze how to identify when gaming is possible in light of (i) how tightly the decision-making proxies are tied to the factors that would ideally determine the outcome, (ii) how easily those proxies can be altered by decision subjects, and (iii) whether such strategic alterations ultimately lead to mistaken decisions. Based on this analysis, we argue that blanket claims that disclosure will lead to gaming are over-blown and that it will often be possible to construct socially beneficial disclosure regimes.